(untitled) - Lee, Dong Sun (Boca Raton, 2008)
the Food Packaging Science and Technology covers basic principles and technologies as well as advanced topics such as active, intelligent, and sustainable packaging with unparalleled depth and breadth of scope. Emphasizing the application of relevant scientific principles to create effective designs and quality products, an international team of contributors draws on their collective experience to equip you with the necessary knowledge and tools to tackle modern food packaging problems
Keywords: Thực phẩm,Food; Quy trình đóng gói,Packaging